Effect of Curcuma longa freeze dried rhizome powder with milk in STZ induced diabetic rats - Rai, P. K. (Springer-Verlag, 2010)
This study deals with the effects of freeze dried rhizome powder of Curcuma longa (C. longa) dissolved in milk on normal as well as diabetic models. Diabetes of type II and type I was within 3 days of a single administration of doses of 45 and 65 mg kg(−1) of streptozotocin respectively. Various parameters such as blood glucose levels, triglycerides, total cholesterol, high density lipoprotein, very low density lipoprotein, low density lipoprotein, serum glutamic oxaloacetic transaminase, serum glutamic pyruvate transaminase, alkaline phosphatase, creatinine, hemoglobin, urine protein and urine sugar in addition to body weight were taken in to consideration and were analyzed after administration of variable doses of rhizome powder. The dose of 200 mg kg(−1) was identified as the most effective dose as it increased HDL, Hb and bw (P<0.05) with significant decrease in the levels of blood glucose, lipid profile and hepatoprotective enzymes (P<0.001).